Cronobacter spp. as emerging causes of healthcare-associated infection - Holý, Ondřej; Forsythe, S (The Journal of hospital infection, 2014)
BACKGROUND: Until recently, members of the Cronobacter genus (formerly known as Enterobacter sakazakii) were a relatively unknown cause of nosocomial infections. However, their association with infant infections, particularly through the consumption of contaminated reconstituted infant formula in neonatal intensive care units, has resulted in international efforts to improve neonatal health care. AIM: To investigate current understanding of this emergent group of bacterial pathogens and the steps taken to reduce neonatal infection. METHODS: A literature review was undertaken to determine current knowledge of the Cronobacter genus with respect to recent taxonomic revisions, sources and clinical relevance. FINDINGS: The majority of severe neonatal meningitis infections are associated with one of the 10 Cronobacter spp., the clonal complex known as C. sakazakii sequence type 4. International efforts by the Food and Agriculture Organization-World Health Organization (WHO) to reduce the risk of neonatal infection by this organism have resulted in improved microbiological safety of powdered infant formula (PIF), but revised guidelines for feeding practices have been problematic. In addition, the majority of infections occur in the adult population and the sources are unknown. CONCLUSION: International improvements in the microbiological safety of PIF and advice on feeding practices have focused on improving neonatal health care following the heightened awareness of Cronobacter infections in this particular age group. These measures are also likely to reduce neonatal exposure to other opportunistic bacterial pathogens, but a number of unresolved issues remain with respect to the practicalities of feeding premature neonates safely while following WHO advice.
Keywords: Communicable Diseases, Emerging; meningitida bakteriální; Infant; Meningitis, Bacterial; novorozenec; Infant Formula; zdravotnická zařízení; lidé; objevující se infekční nemoci; Infant, Newborn; nemoci přenášené potravou; Health Facilities; Cronobacter; Cross Infection; kojenec; náhražky mateřského mléka; infekce spojené se zdravotní péčí; Enterobacteriaceae Infections; Foodborne Diseases; enterobakteriální infekce; Humans